Genome Size Variation across a Cypriot Fabeae Tribe Germplasm Collection - Charalambous, Iliana; Ioannou, Nektaria; Kyratzis, Angelos C.; Kourtellarides, Dimitrios; Hagidimitriou, Marianna; Nikoloudakis, Nikolaos (My University, 2023)
DNA content is an important trait linked to the evolutionary routes of taxa and often connected to speciation. In the present study, we studied C-values variation across the Cypriot Fabeae gene pool. Several hundred plants (Vicia spp., Lens spp., Pisum spp.) were sampled across Cyprus. Accurate estimates were established by flow cytometry and propidium iodine staining for 155 discrete populations/accessions. A ten-fold variation was detected across lineages with 1C DNA content varying from 1.584 pg for V. cretica (ARI02420) to 13.983 pg for V. faba (ARI00187). In general, flow cytometry was precise for the characterization of species, even though there were instances of genome overlapping across taxa. Most analyses in the current work refer to species that have not been characterized before by flow cytometry (or any other DNA content estimation method). Still, a correlation to C-values previously reported in Kew Plant DNA C-values database was attempted. A high degree of correlation except for V. dalmatica was established. The evaluation of genome size trait in relation with the Fabeae phylogeny, revealed that Pisum and Lens genera were rather homogenous, but an astonishing fluctuation was shown for Vicia spp. Moreover, it was established that genome up- or down-scaling was not directly linked to speciation drivers. The genomic size measurements presented here could deliver extra quality control for the identification and characterization of taxa in germplasm collections, particularly in cases where species share morphological characters.
Keywords: C-value; DNA content; flow cytometry; genetic resources; legumes